WAYS TO IMPROVE DIAGNOSIS, TREATMENT AND PREVENTION OF DISEASES OF CHILDREN WITH ATOPIC CHEILITIS - Khafizova D.B. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Many dentists have difficulty making a diagnosis and choosing a treatment method for people with atopic cheilitis . Clinical picture of atopic Cheilitis is characterized by the involvement of the red border of the lips in the pathological process and damage to the skin of the perioral part of the lips, most intense in the area of the corners of the mouth, which manifests itself in the form of its infiltration and lichenification . In this article we talked about the diagnosis, treatment and prevention of atopic cheilitis .